2019
DOI: 10.1111/ans.15379
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is an independent predictor of delayed gastric emptying following pancreaticoduodenectomy: a retrospective study

Abstract: Background: The pathogenesis of delayed gastric emptying (DGE), a common complication of pancreaticoduodenectomy, is unclear. Loss of skeletal muscle mass (sarcopenia) is associated with post-pancreaticoduodenectomy complications; however, few studies have investigated the relationship between sarcopenia and DGE. The aim of this study was to investigate whether post-pancreaticoduodenectomy DGE is affected by pre-operative skeletal muscle mass. Methods: We retrospectively analysed the data of 112 consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Postoperative ileus is a common complication. Previous studies have demonstrated a relationship between sarcopenia and delayed gastric emptying in patients undergoing PPPD [ 29 , 30 ], which could be one possible reason for increased risk of PONV in sarcopenic patients in current study. An association between sarcopenia and nausea has been reported in patients with cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 58%
“…Postoperative ileus is a common complication. Previous studies have demonstrated a relationship between sarcopenia and delayed gastric emptying in patients undergoing PPPD [ 29 , 30 ], which could be one possible reason for increased risk of PONV in sarcopenic patients in current study. An association between sarcopenia and nausea has been reported in patients with cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 58%
“…First, most patients with severe sarcopenia have low physical activity, which is associated with impaired gallbladder motility, leading to increased prevalences of gallstones (including sludge) and RBO 39,40 . Second, Sarcopenia is an independent predictor of delayed gastric emptying, leading to increased prevalences of food impaction and RBO 41 . Third, sarcopenia is a signi cant predictor of poor chemosensitivity and survival in patients with unresectable cancer.…”
Section: Discussionmentioning
confidence: 99%